2022
DOI: 10.3389/fphar.2022.975816
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy evaluation of Buyang Huanwu Decoction in the treatment of ischemic stroke in the recovery period: A systematic review of randomized controlled trials

Abstract: Background and purpose: Buyang Huanwu decoction (BYHWD) is widely used in the treatment of ischemic stroke in the recovery period, and many clinical trials have been reported, but its clinical efficacy and safety have not been fully evaluated. In this study, we conducted a systematic review and meta-analysis to evaluate the clinical efficacy and safety of BYHWD in the recovery period.Materials and methods: Eight databases, including CNKI, Wanfang Database, VIP Database, China Biomedical Literature Database, Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Pharmacological studies have shown that the mechanisms of BYHWD in the treatment of IS are mainly related to promoting vascular and neural regeneration, anti‐atherosclerosis, anti‐inflammatory, BBB protection, mitochondrial protection, and anti‐platelet aggregation (Chen et al, 2020; Wang et al, 2021). A meta‐analysis of 39 studies showed that BYHWD combined with conventional treatment for IS is more effective in reducing NIHSS and improving ADLs than conventional treatment (Wang, Ren, et al, 2022).…”
Section: Ameliorative Effect Of Tcm Formulas On Ismentioning
confidence: 99%
“…Pharmacological studies have shown that the mechanisms of BYHWD in the treatment of IS are mainly related to promoting vascular and neural regeneration, anti‐atherosclerosis, anti‐inflammatory, BBB protection, mitochondrial protection, and anti‐platelet aggregation (Chen et al, 2020; Wang et al, 2021). A meta‐analysis of 39 studies showed that BYHWD combined with conventional treatment for IS is more effective in reducing NIHSS and improving ADLs than conventional treatment (Wang, Ren, et al, 2022).…”
Section: Ameliorative Effect Of Tcm Formulas On Ismentioning
confidence: 99%
“…Buyang Huanwu (BYHW) decoction containing Chishao is also a traditional Chinese medicine compound preparation. Relevant clinical studies and meta-analysis have proved that its therapeutic effect on stable angina pectoris (SAP)and stroke ( Zhang et al, 1995 ; Gao et al, 2021 ; Wang et al, 2022a ). Recently, Wang et al (2022b) designed a randomized, blinded, parallel controlled, multicenter clinical trial to compare the efficacy and safety of NXT and BYHW in the treatment of SAP.…”
Section: Clinical Applicationmentioning
confidence: 99%
“…Previous systematic reviews and meta-analyses have consistently demonstrated the efficacy and safety of BYHWD for treating ICH. [ 24 , 25 ]. As a neuroprotective agent, BYHWD modulates the non-classical NF-κB pathway, attenuating the inflammatory response following ICH [ 23 ].…”
Section: Introductionmentioning
confidence: 99%